Lectotype designation of the name Hieracium loscosianum (Asteraceae) - Ferrer-Gallego, P. Pablo; Mateo, Gonzalo; Sáez, Llorenç; Rosselló, Josep A. (Phytotaxa, 2022)
The name Hieracium loscosianum Scheele is lectotypified using a specimen preserved at COI herbarium.